التشكيل الجمالي للثنائيات الضدية في الصورة الشعرية (شعر أبي تمام أنموذجا) - محمد الأمين, فارسي (جامعة الوادي - University of Eloued, 2021)
إنّ اللّغة بوصفها منظومة تقوم على مبدأيْ التّماثل والاختلاف, فلا غرابة حين يتّكئ المنشئ على هذه الخصائص, مُستفيداً ممّا تُتيحه من إمكانات, وعند هذا المستوى يقع الاختلاف بين المُبدع وغيره؛ لأنّ لغة الشّعر تمتاز بِسِمات مُعيّنة, الأمر الذي اِستغلّه المبدع وبطريقة تُخرجها مركّبَة, تركيباً مُخالفا لطبيعتها, فتجعل منها بتألُفِها مع غيرها, شعريّة مُتميّزة, فيصبو النّصّ بها إلى الوقوع على أواصر الانتساب إلى الأدب بما هو اختيار واعٍ لأدوات التّعبير. لذلك تأتي هذه الدّراسة لمناقشة ما تُشكِّلُه هذه الثّنائيات الضّدّية من جمالية وخاصّة على مستوى الصّورة الشّعرية. حين يمنح الشّاعر الألفاظ معان جديدة لم تكن لها, وقد يَخرِق قاعدة لغوية مدفوعاً بحسّه الفنّي, فلا يُسيء إلى اللّغة, وإنّما يشدّها إلى الأمام. وهنا نتساءل : كيف تأخذ الكلمة مفهوم السّحر؛ لتؤثّر في العقول ؟ ومدى هذا التّأثير ؟ وهل اللّغة بعد ذلك نِعمة أو نِقمة ؟ الكلمات المفتاحية : اللّغة, التّماثل, الاختلاف, شعرية, اختيار, الثّنائيات, الصّورة . Abstract : Language, being described as a system, is based on two principles: symmetry and difference. It's no surprise when the creator relies on these principles taking benefits from the many possibilities offered by the former and on this level lies the difference between the inventive writer and the others; because poetic language is characterised by specific traits. This is exploited by the inventive writer or poet in a way to come up with a complex outcome, a combination different from what is essentially designed for and makes it in correlation with other words, poetically special. Thus the text aims at falling into the bonds of closeness to literature as a mindful choice of expression tools. Therefore this study comes to discuss the aesthetics of these anti-dichotomies, especially on the level of poetic imagery, where the poet provides his words with new meanings they weren't originally theirs. He even may break a linguistic rule driven by his artistic spirit, without doing any harm to language however he fosters it forward and here comes the question: How do a word get the essence of magic to affect minds ? and what's the extent of this effect ? and is language then a blessing or a curse ? key words: language; symmetry; difference; poetic; choice; dichotomy; image.
مقال
Keywords: اللغة-التماثل-الاختلاف-شعرية-اختيار-الثنائيات.